2020
DOI: 10.1007/s10198-020-01222-8
|View full text |Cite
|
Sign up to set email alerts
|

How French general practitioners respond to declining medical density: a study on prescription practices, with an insight into opioids use

Abstract: Disparities in physicians' geographical distribution lead to highly unequal access to healthcare, which may impact quality of care in both high and low-income countries. This paper uses a 2013-2014 nationally representative survey of French general practitioners (GPs) matched with corresponding administrative data to analyze the effects of practicing in an area with weaker medical density. To avoid the endogeneity issue on physicians' choice of the location, we enriched our variable of interest (practicing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…ones; 11 and GPs with higher workloads tend to prescribe medication more often and spend less time with their patients than doctors with lower workloads. 12 Specifically concerning vaccination, our previous work showed that GPs younger than 50 y, female, or with the highest workloads tend to recommend the vaccines on the official schedule more frequently to patients than the others. 3 In contrast, female HCPs (GPs and nurses) and those aged younger than 40 y expressed hesitation about upcoming COVID-19 vaccines more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…ones; 11 and GPs with higher workloads tend to prescribe medication more often and spend less time with their patients than doctors with lower workloads. 12 Specifically concerning vaccination, our previous work showed that GPs younger than 50 y, female, or with the highest workloads tend to recommend the vaccines on the official schedule more frequently to patients than the others. 3 In contrast, female HCPs (GPs and nurses) and those aged younger than 40 y expressed hesitation about upcoming COVID-19 vaccines more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Der demografische Wandel betrifft auch die Leistungserbringer des Gesundheitswesens: Zur Aufrechterhaltung des Versorgungsniveaus von 2016 müssten bis 2035 etwa 146.000 Ärzte altersbedingt ersetzt werden [ 9 ]. Ähnliche Probleme zeigen sich auch im Nachbarland Frankreich: Hier wird die Versorgung in strukturschwachen Gegenden mit bereits pensionierten, jedoch weiterhin behandelnden Ärzten aufrechterhalten [ 10 ]. Die bisherige Versorgungsdichte in Deutschland (4,3 Ärzte bzw.…”
Section: Intersektoralitätunclassified
“…We focus on general practitioners (GPs) since, in France, slightly less than 90% of opioid prescribers are GPs [ 2 ]. Silhol et al [ 62 ] also show that, in France, GPs practicing in the so-called ‘medical deserts’ (geographical areas characterized by low doctors’ density) tend to prescribe more opioid analgesics. Finally, medical density can also be viewed as a proxy for accessibility to healthcare services.…”
Section: Econometric Analysismentioning
confidence: 99%